2013
DOI: 10.3389/fnhum.2013.00608
|View full text |Cite
|
Sign up to set email alerts
|

Methodological lessons in neurophenomenology: Review of a baseline study and recommendations for research approaches

Abstract: Neurophenomenological (NP) methods integrate objective and subjective data in ways that retain the statistical power of established disciplines (like cognitive science) while embracing the value of first-person reports of experience. The present paper positions neurophenomenology as an approach that pulls from traditions of cognitive science but includes techniques that are challenging for cognitive science in some ways. A baseline study is reviewed for “lessons learned,” that is, the potential methodological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 21 publications
1
33
0
2
Order By: Relevance
“…For instance, it has been found that participants who recalled an experience of awe reported feeling smaller relative to the environment, as measured through self-report questionnaires [7]. People who watched the Earth from space by using a virtual reality (VR) simulation reported feelings of awe and feeling small and insignificant in the face of the vast and incomprehensible universe [19,20]. In addition, in a recent study experimentally induced feelings of awe resulted in higher ratings on the "small-self-scale," consisting of items like 'I feel small or insignificant' and 'I feel the presence of something greater than myself' [8].…”
Section: Original Research Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it has been found that participants who recalled an experience of awe reported feeling smaller relative to the environment, as measured through self-report questionnaires [7]. People who watched the Earth from space by using a virtual reality (VR) simulation reported feelings of awe and feeling small and insignificant in the face of the vast and incomprehensible universe [19,20]. In addition, in a recent study experimentally induced feelings of awe resulted in higher ratings on the "small-self-scale," consisting of items like 'I feel small or insignificant' and 'I feel the presence of something greater than myself' [8].…”
Section: Original Research Reportmentioning
confidence: 99%
“…Next, participants completed the same 8 awe manipulation check items as used in the first two studies (Cronbach's a = .97). Participants also completed a shortened version of the Tellegen absorption scale, consisting of 15 items (corresponding to the following items from the original scale: 3,4,7,8,9,10,12,14,16,19,21,24,25,28,31) 8 using a 4-point Likert scale (Cronbach's a = 83). The rationale for using a shortened version of the absorption scale was to save time, as previous research had shown that the shortened version had similar psychometric properties as the extended version (van Elk & Lindeman, in prep.).…”
Section: Stimuli and Experimental Proceduresmentioning
confidence: 99%
“…Interpretation will arise from participants' own words (42), thus researchers can be free of preconceptions and let the natural flow of the conversation organize participants' subjective experiences into quantifiable domains. The 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 11 psychometric constructs that will be designed based on this intuitive structure could in turn be used as one level of verification in future research (34).…”
Section: A Neurophenomenological Remedymentioning
confidence: 97%
“…The codes, subcategories and themes that hermeneutic research would yield could be validated scientifically by objective measurements of brain activity via functional neuroimaging/EEG (34). Conversely, the results from the phenomenological analysis could be used to heuristically interpret individual differences in neural activity associated with NS reaction patterns (30).…”
Section: A Neurophenomenological Remedymentioning
confidence: 99%
See 1 more Smart Citation